Los paradigmas educativos vigentes en el centro educativo intercultural bilingüe Lautaro de la comunidad Sunikilak, cantón Pujili, provincia de Cotopaxi - Duque Guanotuña, Rodolfo José (2015)
This research work is the result of the claim of current education paradigms of community education Intercultural Bilingual Education Center "Lautaro" the Sunikilak community, parish Angamarca, Pujilí province of Cotopaxi. For which a survey that collects information and data relevant educational models proposed in the "Lautaro" School and how they influence the teaching-learning process and the educational community was applied. In addition to the institutional vision outlined by the aforementioned school, which offers students a quality education that contributes to social justice and form them as competent subjects in the full development of their skills and as a result access to better living conditions and learn to live in solidarity and democratic. From the vision of the "Lautaro" school, allows teachers, students and parents think about the relevance of research and investigates and explains how this education from a pedagogical look determined in this way and the educational structure progress of the community. Considering that the research was conducted in rural, low socioeconomic status and students' homes lack sufficient means for a decent life; income barely meets the basic needs of the community in food, health, housing and education. Most of the parents are engaged in agriculture, and migration is the choice of life.